АНАЛІЗ ДІЯЛЬНОСТІ СОЦІАЛЬНИХ ФАХІВЦІВ У НІМЕЧЧИНІ В КОНТЕКСТІ ЇХ ПРОФЕСІЙНОЇ ПІДГОТОВКИ ДО РОБОТИ ЗІ СІМ’ЄЮ - Дужа-Задорожна, Мирослава; Голуб, Іванна (Збірник наукових праць Уманського державного педагогічного університету, 2020)
У статті розглянуто особливості діяльності представників різних типів соціальних професій в Німеччині. Особлива увага звертається на фахівців з догляду за дітьми і з догляду за сім’єю, вихователя, дошкільного педагога, соціального працівника і соціального педагога, сфера діяльності яких передбачає надання різних видів соціальних послуг сім’ї. На основі аналізу нормативно-навчальної документації охарактеризовано процес професійної підготовки німецьких соціальних фахівців до сімейно орієнтованої діяльності на різних освітньо-професійних рівнях. В статье рассмотрены особенности деятельности представителей различных типов социальных профессий в Германии. Особое внимание обращается на специалистов по уходу за детьми и по уходу за семьей, воспитателя, дошкольного педагога, социального работника и социального педагога, сфера деятельности которых предусматривает предоставление различных видов социальных услуг семье. На основе анализа нормативно-учебной документации исследован процесс профессиональной подготовки немецких социальных специалистов к семейно ориентированной деятельности на разных образовательно-профессиональных уровнях. The article examines the peculiarities of the multi-aspect work of different types of social professions representatives in Germany in the context of their training to work with the family. Particular attention is paid to specialists in child care and family care, educators, nursery school teachers, social workers and social educators, the scope of work of which provides various social and educational services to children, youth and families. Based on the analysis of the academic documentation, professional literature and practical experience it was revealed that for staffing of this work a differentiated, hierarchically ordered structure of the training of social professionals in four educational and professional levels is used in Germany. This article describes the process of training of German social experts to family oriented activities in different types of educational institutions of secondary special and higher education.